Sztuka hejtu. Powtórzenia, parafrazy i „cytatowość” w filmie Sala samobójców. Hejter Jana Komasy - Miławska-Ratajczak, Małgorzata (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The aim of this article is to present stylistic measures dominating in a movie directed by John Komasa, The Hater, whose screenplay was written by Mateusz Pacewicz. Komasa’s film is an interesting example of how the selection of linguistic means and the way they function within one work can create an illusory, film version of “the art of hating” – the main impression of all the manipulations used by the film’s protagonist. Forms of manipulation, aggression, hate speech or Internet hate in The Hater’s verbal layer are particularly clearly heard thanks to repetitions, paraphrases and a very specific stylistic manoeuvre, which can be called “quotations.”